Dançando com o cinema, filmando a história: a trajetória crítica de Rogério Sganzerla - Silva, Gilmar Alexandre da (2008)
The aim of this study is to analyse the film critic Rogério Sganzerla s historical trajectory (1946-2004). Thus, film reviews will be approached as well as the critic s own films and his influence upon the film industry plus the historical and cultural relationship established between this movie maker and Brazil. By tracing history and the cinema, we try to understand some aspects of the Brazilian society such as the political and cultural ones, meddled with Rogério Sganzerla s restless and polemic trajectory, and which could furnish some clues on the different directions through which the history of the country has undergone. Hence, the objective of this work is to comprehend, through Rogério Sganzerla s productions, the importance of his labor for the Brazilian movie within a broader purpose, whichever is, Sganzerla s roll with the cinema, Brazil, and himself.